Pengaruh Perceived Organizational Support, Contigency Reward Behaviour terhadap Work Engagement - Fildzah Aleyda; Dita Oki Berliyanti (Jurnal Akuntansi, Keuangan, dan Manajemen, 2023)
Purpose: This study aimed to analyze and explore the presence of perceived organizational support and contingent reward behavior in work engagement case studies of employees in PT Pelabuhan Indonesia. Methodology: The sample used in this study was purposive by distributing questionnaires online to 70 employees at PT Pelabuhan, Indonesia. The data analysis method was a simple regression method using SPSS version 25. Results: The results showed that perceived organizational support and contingent reward behavior had a positive and significant effect on work engagement in a case study of employees in PT Pelabuhan Indonesia. Limitations: This study involved only 70 employees at PT Pelabuhan Indonesia as respondents. In this study, only contingency reward behavior and perceived organizational support were used as independent variables. Work engagement is the dependent variable. Contribution: The findings of this study are useful in providing and becoming a source of information about the influence of perceived organizational support and contingent reward behavior, and can be applied by PT Pelabuhan Indonesia so that they can pay more attention to employees by implementing contingent reward behavior and perceived organizational support so that workers will feel valued in working at PT. Pelabuhan Indonesia feels that the workforce is prioritized, gets motivated, and can be rewarded according to performance to achieve company goals. This will have an impact on increasing work engagement in PT Pelabuhan, Indonesia.